Compilation of Quranic verses related to visual function - Badarudin, Noor Ezailina; Yazid, Yazlin; Md Halim, Siti Aishah; Mohamad, Hasbullah (2016)
The creation of the visual system is a precious gift whereby the eyesight bestowed by Allah upon us allows the daily activities to be conducted easily and efficiently. Allah reminds us in the Quran to be thankful for all the senses that we have, "It is He, Who has created for you (the sense of) hearing (ears), sight (eyes), and hearts (understanding). “Yet, only few of you are grateful" (23:78). According to Prophet Muhammad (SAW), “Allah The Almighty said, ‘If I take away the eyesight of a slave of Mine and he shows patience and seeks My reward, then I shall reward him with nothing less than paradise’” (Sahih Al-Bukhari). The objects we see every day emit light rays which enter our cornea and refracted on to the retina that contains millions of tiny light-sensing nerve cells (Rajendra, Eddie & Jasjit, 2008). These nerve cells will convert the light stimulus into electrical impulses which will then be transmitted by the optic nerve to the brain that produces the images we see. Thus, the objects seen are actually the reflection of light that serves as a proof of a great creation of our Creator as stated in the Holy Quran, “Allah is the Light of the heavens and the Earth” (24:35). There are limited writings on visual functions which refer to the Quran and Hadiths. Thus, this qualitative study aims to compile all the Quranic verses and Hadiths of Sahih Bukhari related to visual function by referring to the words “light”, “eye/s” and “sight (and its synonyms)”; which allows their frequency to be identified. Search for the related Quranic verses is performed by using a website (www.searchtruth.com) The compiled words are later associated with the fundamentals of the visual functions based on scientific articles, in order to prove how these divine revelations may serve as a reference for Muslim and interested non-Muslim optometrists in treating their patients.